Новые материалы каменного века из долины р. Кучурган - Киосак, Д.В. (Материалы по археологии Северного Причерноморья, 2011)
The paper presents new lithic collections, both from already known and newly discovered sites. They were mostly uncovered by research done by field survey team of Odessa Archaeological Museum in 2009-2011. Four sites Zalz, Zalz 1 and Varvara 1 and 2 could be attributed to Paleolithic. New abundant finds were provided by Recent Mesolithic Grebenyky site. A group of sites revealed in the vicinity of Frunzivka (Zaharivka 1, la, 6) bear microlithic inventory typical for Recent Mesolithic and Neolithic. The largest collection (Zaharivka 1) yielded some components characteristic for Middle and Recent Neolithic.